The Effect of Islamic Service Quality and Trust on Member Loyalty at BMT UGT Nusantara Capem Muncar Banyuwangi Regency - Nisa, Ifatun; Khusnudin, Imam (Jambura Economic Education Journal, 2025)
This research examines the impact of Islamic service quality and trust on member loyalty at BMT UGT Nusantara Capem Muncar in Banyuwangi Regency. Using a quantitative approach, the study employs purposive sampling to gather data from 80 respondents. Primary data is collected through Likert-scale questionnaires and analyzed using multiple linear regression. The findings reveal that both service quality (X1) and trust (X2) significantly influence member loyalty. The t-test results show t-values of 4.623 (sig. 0.001) for service quality and 20.758 (sig. 0.001) for trust. Additionally, the F-test yields an F-value of 226.125 (sig. 0.001), confirming that both variables collectively and individually have a positive effect on member loyalty.